Needs analysis of character education training for teachers at Multi Dimensi vocational school - Ulfia Nanda Maulia; Abubakar Abubakar; Asep Dikdik; Cucun Hasanah (Inovasi Kurikulum, 2025)
The importance of character education in the context of teacher role modeling for students in the context of moral and ethical instruction has been well-documented. However, a paucity of research has been conducted on implementing character education in SMK Multi Dimensi Anyer. Therefore, a needs analysis was performed to identify the gap between the current competencies of teachers. This research aims to overcome the problem through the Training Needs Survey approach and recommends a development design for strengthening teacher character education by conducting training. The research method employed in this study is a descriptive exploratory approach, incorporating qualitative and quantitative (mixed) methods, with data collection techniques including observations and interviews conducted with the principal and deputy head of curriculum to identify character education needs for teachers and the administration of questionnaires analyzed with IBM SPSS Statistics 26 to measure the understanding and application of character education by teachers. The results of the interviews indicated a need for training to enhance character education, and the results of the questionnaire distribution demonstrated that only two teachers attained the ideal score based on the level calculation on 18 sub-indicators, with a score above 55, and an overall average score of 49.3 was obtained. The findings reveal a discrepancy, indicating the necessity for training to enhance teachers' competence in instilling student character values.   Abstrak Pendidikan karakter penting diterapkan oleh guru agar dapat menjadi teladan bagi peserta didik dalam menanamkan moral dan etika. Namun, banyak guru belum menerapkannya di SMK Multi Dimensi Anyer. Sehingga, analisis kebutuhan diperlukan untuk melihat kesenjangan antara kompetensi guru saat ini.Tujuan penelitian ini untuk mengatasi permasalahan melalui pendekatan Training Needs Survey dan merekomendasikan sebuah rancangan pengembangan penguatan pendidikan karakter guru dengan mengadakan sebuah pelatihan. Metode penelitian yang digunakan dalam penelitian ini adalah deskriptif eksploratif dengan pendekatan kualitatif dan kuantitatif (campuran) dengan teknik pengumpulan data berupa observasi dan wawancara berbeda yang dilakukan dengan kepala sekolah dan wakil kepala kurikulum untuk mengidentifikasi kebutuhan pendidikan karakter bagi guru dan penyebaran kuesioner dianalisis dengan IBM SPSS Statistics 26 untuk mengukur pemahaman dan penerapan pendidikan karakter oleh guru. Hasil wawancara menunjukkan bahwa pelatihan yang dibutuhkan adalah penguatan pendidikan karakter dan hasil penyebaran kuesioner menunjukkan bahwa hanya terdapat dua guru yang memenuhi nilai ideal berdasarkan kalkulasi level pada 18 sub-indikator, dengan score diatas 55 dengan rata-rata score keseluruhan yang diperoleh sebesar 49,3. Demikian, hasil keseluruhan menunjukkan kesenjangan, sehingga pelatihan diperlukan untuk meningkatkan kompetensi guru dalam menanamkan nilai karakter pada peserta didik. kata kunci: analisis kebutuhan; pelatihan guru; pendidikan karakter; pengembangan profesional; sekolah kejuruan